Anti-Müllerian hormone in health and disease: a review - Sirsikar, Mangala; Pinnelli, Venkata Bharat Kumar; Mohanty, Shrabani; C. A., Jayashankar (International Journal of Research in Medical Sciences, 2017)
Anti-Müllerian hormone (AMH) is a homodimeric glycoprotein, member of the transforming growth factor β family of growth and differentiation factors. In the ovary, AMH has an inhibitory effect on primordial follicle recruitment as well as on the responsiveness of growing follicles to follicle-stimulating hormone (FSH). The ovary-specific expression pattern in granulosa cells of growing non-selected follicles makes AMH an ideal marker for the size of the ovarian follicle pool. AMH levels accurately reflect the ovarian follicular reserve and could, therefore, be considered as an extremely sensitive marker of ovarian aging and a valuable tool in the diagnosis and the recognition of recurrence of granulosa cell tumors. Furthermore, AMH could be a surrogate diagnostic marker of polycystic ovary syndrome in cases in which ultrasonographic examination is not possible. Additionally AMH evaluation is of clinical importance in predicting the success of in vitro fertilization (IVF). Special reference is made to the possible implications of AMH in the pathogenesis of polycystic ovary syndrome and the relationship between AMH and obesity. AMH also plays important role in evaluation of infants with ambiguous genitalia and other intersex conditions. This article is a review of the clinical usefulness of AMH evaluation in the fields of gynecological endocrinology, menopause, gynecological oncology and assisted reproduction and also in pediatric patients.